Pengembangan Lembar Kerja Peserta Didik Berbasis Contextual Teaching and Learning - Tina Aprillia; Elya Rosalina; R Angga Bagus Kusnanto (Journal of Elementary School (JOES), 2023)
This study aims: (1) to produce a CTL-based LKPD that is valid for use in Mathematics learning flat shape material for class IV SD Negeri 2 Air Lesing. (2) to find out the practicality of using CTL-based LKPD in learning Mathematics on flat shape material for class IV SD Negeri 2 Air Lesing. This research is included in research and development (R&D). The research uses the ADDIE development model which consists of 5 stages of development, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used are observation, interviews, and questionnaires (questionnaires). The results showed that the CTL-based LKPD had a validity level of 0.81 which was categorized as high or valid for use in the learning process. CTL-based LKPD also has a practicality level of 88% with a very practical category. Based on the results of the development research above, it can be concluded that the developed CTL-based LKPD is valid and practical. Keywords: Development, CTL-based LKPD. ADDIE Math.